2014
DOI: 10.1371/journal.pgen.1004641
|View full text |Cite
|
Sign up to set email alerts
|

The Association of the Vanin-1 N131S Variant with Blood Pressure Is Mediated by Endoplasmic Reticulum-Associated Degradation and Loss of Function

Abstract: High blood pressure (BP) is the most common cardiovascular risk factor worldwide and a major contributor to heart disease and stroke. We previously discovered a BP-associated missense SNP (single nucleotide polymorphism)–rs2272996–in the gene encoding vanin-1, a glycosylphosphatidylinositol (GPI)-anchored membrane pantetheinase. In the present study, we first replicated the association of rs2272996 and BP traits with a total sample size of nearly 30,000 individuals from the Continental Origins and Genetic Epid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 63 publications
1
15
0
Order By: Relevance
“…Thirty single nucleotide polymorphisms (SNPs) were selected for genotyping and association analysis with BP. These SNPs were selected based on the previous association evidence with BP from GWASs or admixture mapping analysis 23,[25][26][27][28][29] (Table S1, Supporting Information).…”
Section: Candidate Single Nucleotide Polymorphism Selectionmentioning
confidence: 99%
“…Thirty single nucleotide polymorphisms (SNPs) were selected for genotyping and association analysis with BP. These SNPs were selected based on the previous association evidence with BP from GWASs or admixture mapping analysis 23,[25][26][27][28][29] (Table S1, Supporting Information).…”
Section: Candidate Single Nucleotide Polymorphism Selectionmentioning
confidence: 99%
“…Because of the roles of GPI-APs in prominent human diseases, including malaria ( Davidson and Gowda, 2001 ) and neurodegenerative prion diseases ( Puig et al, 2014 ; Victoria and Zurzolo, 2015 ), the intracellular quality control of selected GPI-APs has been studied extensively. Various misfolded GPI-APs accumulate in the presence of proteasome inhibitors, suggesting that ERAD is involved in their turnover ( Ma and Lindquist, 2001 ; Yedidia et al, 2001 ; Petris et al, 2014 ; Wang et al, 2014 ). However, this view was challenged by the observation that the proteasome also degrades nontranslocated species, and recent studies suggested that ER-localized misfolded GPI-APs are predominantly routed to lysosomes for degradation ( Drisaldi et al, 2003 ; Ashok and Hegde, 2008 ; Satpute-Krishnan et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Such small molecules or biologicals are named proteostasis regulators; examples include heat shock response activators (7), unfolded protein response activation (8,9), histone deacetylase inhibitors (10), and calcium signaling regulators (11,12). In other cases, aggregation or excess of a protein is associated with diseases; therefore, it would be desirable to promote the degradation of the target protein to ameliorate such disease phenotypes (13,14). It appears that a proteostasis regulator can only work on a number of proteins, presumably because a protein utilizes a subset of proteostasis network components (15, 16), which can be specifically targeted by this proteostasis regulator.…”
Section: Introductionmentioning
confidence: 99%